Pengaruh Stres Kerja dan Pemberdayaan terhadap Kepuasan Kerja Karyawati Call Center di PT X Surabaya - Wuri W., Mei Rahmi; Nugrohoseno, Dwiarko (BISMA (Bisnis dan Manajemen), 2018)
In order to improve the quality of corporate services, much needed work stress control and employee empowerment are expected to increase job satisfaction of employees so that employees who feel satisfied will try to do my best and advance the company. This study aims to determine the effect of job stress and employee empowerment on job satisfaction in PT. X Surabaya. The population in this study is a call center employee PT. X with a sample of 105 respondents. To analyze the data, regression analysis using the program package SPS / IBM PC edition Sutrisno Pamardiningsih Yuni Hadi and 2000. Results of data analysis known that a significant difference between job stress and job satisfaction that has a negative influence, and there is insignificant effect between empowerment and job satisfaction with a correlation coefficient R2 = 0.467 and p = 0.000 with a significance level of 5%. The conclusion is collectively - as a significant difference between job stress and job satisfaction, empowerment with effective contribution that is equal to 46.3%, and amounted to 54.7% influenced by other variables